Research on the Model of Interlayer Melt Blown Non-woven Materials Based on Regression Prediction - Deng, Qianting; Peng, Sitong; Wu, Guanting; Lin, Zhifeng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Melt blown nonwoven materials are currently widely used air filtration materials, with fine fibers, large specific surface area, good fluffiness, multiple pores, and excellent filtration performance. After polar treatment, filtration efficiency can be greatly improved without increasing filtration resistance. Melt blown nonwoven materials are important raw materials for mask production, and their various excellent characteristics have attracted widespread attention from domestic and foreign enterprises. The modeling purpose of this article is to establish a relationship model between process parameters and structural variables, as well as between structural variables and product performance. By combining the given 8 process parameters, the structural variable data can be predicted. Study the relationship between structural variables and product performance, as well as the relationship between structural variables and product performance. And combined with the results, it can be concluded that the filtration efficiency of the product will reach the highest process parameter value.